Ahmadiyya Congregation in the Shadow of Religious Politics: Tensions Between Law and Freedom of Religion - Fadhil, Moh; Sudrajad, Muhammad Rosyad (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The right to freedom of religion is a fundamental right. For Indonesian people, religion is not only seen as a ritual but also as a part of the social relations between society members and the state. However, the sacred value of religion in social relations is degraded through normative recognition in the form of official religious politics. The policy does not actually engender order and justice. On the contrary, official religious political policies and restrictions on religious freedom raise widespread discriminatory practices that affect religious minority groups, such as the Indonesian Ahmadiyya Community. The purpose of this study is to examine the tension between the law and the right to freedom of religion or belief in cases of discrimination against the Ahmadiyya Community of Indonesia from the point of view of the legal theory of legal disorder. The research methods used are socio-legal with a statutory approach, a conceptual approach, and a critical legal study approach using legal disorder theory. This research emphasizes that the Ahmadiyya, as a sect in Islam, has the right to freedom of religion within the Forum Internum. In practice, the official religious politics subordinated the rights of religious freedom under the control of religious majoritarianism. However, empirical facts show that the multireligious social context of Indonesian society places the situation in a state of irregularity. Through the disorder of law theory, Sampford opens the horizons of the legal paradigm, showing that seeing and answering various irregularities cannot be done through the lens of order.